1990
DOI: 10.1136/ard.49.11.896
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarticular brucellosis in children.

Abstract: The findings in 40 children (24 female, 16 male) with osteoarticular complications of bruceliosis are presented. Raw milk was the main source of infection. Most patients had acute onset of fever, arthralgia, and myalgia. Arthritis was the presenting symptom in all patients, of whom two also had osteomyelitis. Arthritis was monoarticular in 28 (70%) of 40 cases with predilection for large weight-bearing joints. Spine and smali joints were spared.Brucella melitensis was detected in 23/31 (74%) cases. Mild anaemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
54
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 20 publications
6
54
0
Order By: Relevance
“…Brucella species are intracellular inhabitants, very di cult to isolate from body¯uids in which they are freed intermittently. 16 Thus it is usually recommended to isolate the microorganism from tissue cultures rather than body¯uids. A CT guided aspiration of the paravertebral abscess may be a useful diagnostic technique but the procedure requires experienced interventional radiologists.…”
Section: Discussionmentioning
confidence: 99%
“…Brucella species are intracellular inhabitants, very di cult to isolate from body¯uids in which they are freed intermittently. 16 Thus it is usually recommended to isolate the microorganism from tissue cultures rather than body¯uids. A CT guided aspiration of the paravertebral abscess may be a useful diagnostic technique but the procedure requires experienced interventional radiologists.…”
Section: Discussionmentioning
confidence: 99%
“…Bones are normally resistant to infections. However, Brucella infection has aspecial tropism for osteoarticular involvement and osteoarticular brucellosis is the most common localization of active disease (2,3,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Focal osteomyelitis of the vertebrae, tibia and especially the knees has also been reported with brucellosis infection even in the absence of other significant systemic symptoms (1, 4, 12-14).…”
Section: Discussionmentioning
confidence: 99%
“…Sanaei-Dashti reported that sacroiliitis is the most common form of the skeletal involvement of brucellosis in adults yet we had no patients with sacroiliitis involvement and most of them showed spondylitis in lumbar vertebra (14). al-Eissa observed no patient with brucellosis spondylitis among 40 children with skeletal complications (15). In a study by Geyik, 24.59% of adults and 17.9% of children who were suffering from skeletal complications of brucellosis had spondylitis (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood culture remains an important investigation and is to be collected preferably in Castenada biphasic medium maintaining meticulous asepsis during the procedure. Treatment with a combination of streptomycin plus tetracyclines or rifampicin results in rapid cure rate and resolution of arthritis without sequelae [4]. In subacute cases, pain in the hip joint may sometimes only be elicited by the Gaenslen and FABERE (Flexion, Abduction, External rotation and Extension) manouvre [2].…”
Section: Discussionmentioning
confidence: 99%